Experimental analysis of outage times for PROFIBUS network - José Augusto Carvalho (2005)
Distributed control systems operation strongly depends on the communication system performance. Therefore, their analysis becomes an important aspect to be considered, particularly in situations where communications have real-time constrains and the network operates on faulty environments. In this paper the behavior of PROFIBUS network in the presence of faults is analyzed. This analysis is performed in an experimental base supported by a real network. The network operation is disturbed through a set of fault injection experiments from which performance metrics related with PROFIBUS outage times are evaluated.